2013
DOI: 10.1103/physrevlett.110.148301
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic Reaction Fronts Inside a Porous Medium of Glass Spheres

Abstract: We analyze experimentally chemical wave propagation in the disordered flow field of a porous medium. The reaction fronts travel at a constant velocity that drastically depends on the mean flow direction and rate. The fronts may propagate either downstream and upstream but, surprisingly, they remain static over a range of flow rate values. Resulting from the competition between the chemical reaction and the disordered flow field, these frozen fronts display a particular sawtooth shape. The frozen regime is like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 19 publications
7
39
0
3
Order By: Relevance
“…They experimentally measured the two scaling exponents α and β for the four regimes and found that those for the SD and AD regimes are consistent with the KPZ-class exponents α = 1/2 and β = 1/3, while for the AS regime + they found 0.6 α, β 0.7, close to the values for the quenched KPZ class [117]. The appearance of the KPZ class and the + In the AS regime, front profiles are eventually frozen, forming a sawtoothlike pattern [116]. At a given time before the complete formation of the final pattern, some parts of the front are already frozen, while others are still evolving.…”
Section: Fronts Of Chemical Waves In Disordered Media Another Very Rementioning
confidence: 72%
“…They experimentally measured the two scaling exponents α and β for the four regimes and found that those for the SD and AD regimes are consistent with the KPZ-class exponents α = 1/2 and β = 1/3, while for the AS regime + they found 0.6 α, β 0.7, close to the values for the quenched KPZ class [117]. The appearance of the KPZ class and the + In the AS regime, front profiles are eventually frozen, forming a sawtoothlike pattern [116]. At a given time before the complete formation of the final pattern, some parts of the front are already frozen, while others are still evolving.…”
Section: Fronts Of Chemical Waves In Disordered Media Another Very Rementioning
confidence: 72%
“…Prominent examples of front propagation include catalytic oxidation of carbon monoxide (CO) on platinum single crystal surfaces [7][8][9][10], arrays of coupled chemical reactors [11], and nematic liquid crystals [12]. Often, the medium that supports front propagation exhibits a complex shape and/or its size is limited like in biological cells [13], nanoporous media [14], or zeolites [15]. In such system the interaction of the reactants with the boundaries of the medium leads to non-intuitive confinement effects [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the flow opposing the front, static fronts have been found depending on the intensity of the the mean flow velocity U that is negative by convention. In previous studies [22][23][24] we have demonstrated that, depending on U , the system display three propagating regimes. If the flow magnitude is high enough, the front recedes downstream.…”
Section: Introductionmentioning
confidence: 78%